Educación y desarrollo local: la universidad intercultural indigena de Michoacán y el desarrollo del municipio de Patzcuaro - Martínez Altamirano, Edgar (Universidad Michoacana de San Nicolás de Hidalgo, 2007)
The target of this investigation was to determine the basic features that it owes to have the Intercultural University Indigenous to Michoacán (UIIM), in order that could turn into an actor with leadership in the local development of indigenous regions, so much in its purposes, in the aspects curriculares and academicians as well as in the ways of operating in the local systems for to generate development. Between the methodological aspects it costs to emphasize that, it was deepened theoretically in order to define variables or factors of economic character, social and cultural, that make the analysis possible most adapted for establishment of proposals directed to the local development. Our investigation has focused also on the experiences analysis in where they predominate over intercultural universities and communities are located natives characterized for having been you of a high degree of alienation and to the date for being provided with a human potential high place that it has all the possibilities of generating local development.

El objetivo de esta investigación fue determinar los rasgos básicos que debe tener la Universidad Intercultural Indígena de Michoacán (UIIM), a fin de que pueda convertirse en un actor con liderazgo en el desarrollo local de las regiones indígenas, tanto en sus finalidades, en los aspectos curriculares y académicos así como en las formas de operar en los sistemas locales para generar desarrollo. Entre los aspectos metodológicos vale destacar que, se profundizó teóricamente a fin de definir variables o factores de carácter económico, social y cultural, que posibiliten el análisis más adecuado para el establecimiento de propuestas encaminadas al desarrollo local. Nuestra investigación se ha enfocado también al análisis de experiencias en donde predominan universidades interculturales y se localizan comunidades indígenas caracterizadas por haber sido víctimas de un alto grado de marginación y a la fecha por contar con un alto potencial humano que tiene todas las posibilidades de generar desarrollo local.
Facultad de Economía Vasco de Quiroga. Maestría en Ciencias en Gestión Estratégica del Desarrollo
Keywords: info:eu-repo/classification/cti/5; FEVAQ-M-2007-0003; UIIM; Pátzcuaro; Michoacán; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4946